Sensitisation of HeLa Cell Cultures to Xanthone Treatment by RNAi-Mediated Silencing of NANOG and STAT3 - Oliwia Gruszka; Dorota Żelaszczyk; Henryk Marona; Ilona Anna Bednarek (Current Issues in Molecular Biology)
The increasing morbidity of various types of cancer in the world’s population and the limited number of universal methods of their treatment contribute to the growth in research into the development of new treatment strategies. Most of this research focuses on treatments that target specific factors in cancer cell signalling pathways. There is also great interest in drugs derived from natural substances, as these represent one of the largest sources of potential pharmaceuticals. In our analysis, we focused on the action of α-mangostin and gambogic acid, which are natural xanthones or their synthetic derivatives. We studied their influence on the expression of STAT3 and NANOG, which play a confirmed role in different stages of cancer development. For this purpose, we applied RNAi-mediated gene silencing of NANOG and STAT3 to enhance the efficacy of xanthone-based anticancer treatment in HeLa cell cultures. After stimulating the cells with xanthones, we determined the expression of the tested transcription factors and the ROS level. In addition, we determined the cytotoxicity and apoptosis of the cells. Our research results confirm the anticancer efficacy of the analysed xanthones and demonstrate the role of the tested transcription factors. Silencing these factors makes cancer cells more susceptible to xanthone treatment.